Psycho social predictors of quality of life among caregivers of cancer patients in the radiotherapy department, UCH, Ibadan (2016)
Anxiety, Depression and Social support) of Quality of Life among caregivers of cancer patients at the University College Hospital, Ibadan. Five instruments were adapted and revalidated for cultural suitability and used to assess social support, quality of life, depression, anxiety and caregivers’ stress. Data were collected from one hundred and fifty one consecutive caregivers of cancer patients who accompanied the patients to the hospital to receive treatment at the radiotherapy department and who gave informed consent to participate in the study. The respondents’ age was ranges between 14 - 72 years with the mean of 35.65 and standard deviation of 14.094. The data collected was analysed using regression analysis and Pearson Product Moment Correlation. A significant negative relationship was found between quality of life and depression in caregivers of cancer patients (P<0.05). Regression analysis indicated that depression significantly predicted the caregivers quality of life (P<0.05). It was recommended that some attention be given to the psychosocial wellbeing of caregivers of cancer patients to enable them have good quality of life and enhance their care-giving role.